Higher Financial Incentives Policy and The Impact to the Employee/s Intention to Leave: A Systematic Literature Review - Puspita, Dynna Dwi (FIA UB, 2019)
The aim of this literature study is to determine the relationship between institutional policies that implement high financial incentives and the employee’s intention to leave. This study is motivated by the result of previous research studies which showed high interest in resigning at the Audit Board of Republic of Indonesia (BPK). Meanwhile BPK loses many employees each year because of the retired, died and resigned. Due to recruiting requires a lot of resources, and then they issue a policy to raise the employee’s financial incentives in order to reduce their employees’s intention to leave. Therefore, this study proposes a framework for studying relation and impact of this higher financial incentive on their employee’s intention to leave. Based on this study, the officials can be using this finding to evaluate the implement of their policy and to take necessary approach in order to reduce high turnover rate in their institution.